9(x-3)-6=2(x+5)+13

Simple and best practice solution for 9(x-3)-6=2(x+5)+13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9(x-3)-6=2(x+5)+13 equation:


Simplifying
9(x + -3) + -6 = 2(x + 5) + 13

Reorder the terms:
9(-3 + x) + -6 = 2(x + 5) + 13
(-3 * 9 + x * 9) + -6 = 2(x + 5) + 13
(-27 + 9x) + -6 = 2(x + 5) + 13

Reorder the terms:
-27 + -6 + 9x = 2(x + 5) + 13

Combine like terms: -27 + -6 = -33
-33 + 9x = 2(x + 5) + 13

Reorder the terms:
-33 + 9x = 2(5 + x) + 13
-33 + 9x = (5 * 2 + x * 2) + 13
-33 + 9x = (10 + 2x) + 13

Reorder the terms:
-33 + 9x = 10 + 13 + 2x

Combine like terms: 10 + 13 = 23
-33 + 9x = 23 + 2x

Solving
-33 + 9x = 23 + 2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2x' to each side of the equation.
-33 + 9x + -2x = 23 + 2x + -2x

Combine like terms: 9x + -2x = 7x
-33 + 7x = 23 + 2x + -2x

Combine like terms: 2x + -2x = 0
-33 + 7x = 23 + 0
-33 + 7x = 23

Add '33' to each side of the equation.
-33 + 33 + 7x = 23 + 33

Combine like terms: -33 + 33 = 0
0 + 7x = 23 + 33
7x = 23 + 33

Combine like terms: 23 + 33 = 56
7x = 56

Divide each side by '7'.
x = 8

Simplifying
x = 8

See similar equations:

| 0=(4x+3)(x-5) | | 4x+6=-5+2x+15 | | 3x^4-6x^3+3=0 | | (x*x)+3x=(x*x)+x | | 5x+20=7x-80 | | (x*x)+3x=(x*x)+x+2 | | 7log(2x+12)=14 | | 7x-3x=15-5 | | (3x^2+2x)+(3x-12)=0 | | 6.6n-60=220 | | 2a-2b=10 | | 2x-37=50 | | 4.2x+35.4=9.8-8.6x | | 0=(8x+9)(x-5) | | 6x=22+4x | | -15=3a-3 | | 8x+35.4=9.8-8.6x | | a^2-1=-7a | | (2x-3)-(x-2)=1 | | x^2-22x+66=0 | | 6x+2=6(x+8) | | y=(7x+6)(x-4) | | 12x+48y-42= | | 5v+40=4v+50 | | 6x+19y=1 | | 12k^2-21=0 | | A=3.14(25) | | 3x-2(2x+2)=5 | | 25v^2=9 | | 2b-4=-6 | | x(4-t^2)=3t-5 | | 32-2s=j |

Equations solver categories